An introduction to the discussion of transposition of the Directive 2024/2831 in the light of the amendments of the Road Transport Act - Klimek, Agnieszka (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
This paper aims to submit duties given to digital labour platforms doing transport services due to amendments to the Road Transport Act of 2001 and responsibilities associated with the transposition of the Directive on improving working conditions in platform work. The author explains why this directive was necessary, bonding working for digital platforms with precarious conditions. Furthermore, changing the Road Transport Act due to taxi service problems wasn’t combined with a simultaneous determination of the legal status of gig workers, which is crucial for them from the point of view of their privileges created by labour law. Then, the author wants to describe why the transposition of the present Directive, especially the legal presumption of an employment relationship, is a problematic solution but is an expected must-have.